Polymer Ionic Liquid Electrolyte for Dye-sensitized Solar Cell - Pang, Zhen Hong (Universiti Teknologi PETRONAS, 2016)
Dye-sensitized Solar Cells (DSSCs) have attracted high interest for the past few year as a new renewable energy technology due to its low cost and simple manufacture process. However, the used of liquid electrolyte in DSSCs had led to some limitation such as toxic, volatile and short lifespan that obstruct the commercialization of the device. Much effort had been done in the study on the electrolyte as the electrolyte brings big impact and influences on the performance of the DSSCs. In this project, Tripropyl Chitosan Iodide (TCI) is synthesized by quaternize the chitosan with propyl chain using Two Step Reaction methodology followed by the formulation of electrolyte using different composition of PMII, PVDF-HFP, TCI and KI/I2.